2020
DOI: 10.1080/09553002.2020.1837984
|View full text |Cite
|
Sign up to set email alerts
|

An overview of potential novel mechanisms of action underlying Tumor Treating Fields-induced cancer cell death and their clinical implications

Abstract: Traditional cancer therapy choices for clinicians are surgery, chemotherapy, radiation and immune therapy which are used either standalone therapies or in various combinations. Other physical modalities beyond ionizing radiation include photodynamic therapy and heating and the more recent approach referred to as Tumor Treating Fields (TTFields). TTFields are intermediate frequency, low-intensity, alternating electric fields that are applied to tumor regions and cells using noninvasive arrays. TTFields have rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 63 publications
0
30
0
Order By: Relevance
“…Mitotic disruption by exogenously imposed electric fields have been reported [ 8 ]; however, mitotic spindles are not the only biological structures that possess intrinsic dipole moments. To illustrate, DNA itself possesses intrinsic dipole moments and recent investigations have revealed that TTFields may have effects on DNA damage response and replication stress, ER stress, membrane permeability, autophagy, and immune response [ 5 ]. In addition, recent modeling studies in the context of dipole alignment suggest that the magnitude of the electric field caused by TTFields may not be sufficient to overcome Brownian motion inherent within the cytoplasm of single cancer cells [ 51 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitotic disruption by exogenously imposed electric fields have been reported [ 8 ]; however, mitotic spindles are not the only biological structures that possess intrinsic dipole moments. To illustrate, DNA itself possesses intrinsic dipole moments and recent investigations have revealed that TTFields may have effects on DNA damage response and replication stress, ER stress, membrane permeability, autophagy, and immune response [ 5 ]. In addition, recent modeling studies in the context of dipole alignment suggest that the magnitude of the electric field caused by TTFields may not be sufficient to overcome Brownian motion inherent within the cytoplasm of single cancer cells [ 51 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advances in techniques to measure voltage and current gradients in biological material coupled with imaging technology to assess morphological changes in organisms have revealed that exposure to electro-magnetic occurrences can trigger a range of morphometric processes from embryological development to wound healing [2][3][4]. Frequencies for biologically relevant exposure to electromotive forces (EMFs) can range from being very low (0-300 Hz) to intermediate values (30 Hz to 400 kHz) to high and very high frequencies (1 MHz to 10 GHz, see Figure 1 [2,5]). Different EMF ranges will initiate different biological effects (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, as far as mentioned above, TTFields enhances autophagy, and increasing autophagy in SARS-COV-2 virally infected cells can lead to apoptosis in them[ 96 , 106 , 107 , 117 ]. Hence, it can be supposed that TTFields can induce apoptosis in SARS-COV-2 virally infected cells subsequently disrupt the viral replication cycle.…”
Section: Tumor Treating Fields Its Benefits and Covid-19mentioning
confidence: 99%
“…But the high recurrence rate usually leads to more restricted treatments and a worse prognosis 2 . Although many pieces of research have presented promising e cacy in their preliminary phases, the majority of phase III clinical trials have failed, including cytotoxic drugs 3,4 , targeted therapies 5-7 , immunotherapies 8,9 , and oncolytic viruses 10 .…”
Section: Introductionmentioning
confidence: 99%